Pembuatan Alat Komposter dalam Mengolah Sampah Menjadi Pupuk Organik di Desa Jenisgelaran. - Dewa Aldiansyah; Qeisha Firmansyah; Atika Permata Sari; Elif Putri Anggraini; Achmad Arsa Abdillah Madjid; Mu’tasim Billah (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
Garbage is a problem that is often faced by the people of Jenisgelaran Village, Bareng District, Jombang Regency. Due to the absence of a proper landfill (TPA), people litter and can cause garbage to accumulate. So that the solution that can be given to the community is to use the waste into organic fertilizer. By making appropriate technology tools in the form of composters that will convert organic waste on a household scale into liquid and solid organic fertilizer. For the manufacture of composter tools, the community is given socialization about the manufacturing procedure to its benefits, composter tools are made on a home scale so that they can be easily applied by the community. Socialization which is a community service program is carried out by providing guide modules, counseling to the provision of one composter tool as an example to the community. The existence of this activity is expected to provide knowledge to the community so that they can process household organic waste into organic fertilizer. It can also provide relief to the community in saving costs to buy fertilizer.